Nodal tumor volume as a prognostic factor for oral squamous cell carcinoma—a systematic review - Bernasconi, Mischa; Bilic, Ante; Kauke-Navarro, Martin; Safi, Ali-Farid (Frontiers in Oral Health, 2023)
Oral squamous cell carcinoma (OSCC) is a complex disease with a high potential for lymph node metastasis and poor survival rates. Accurate nodal staging is crucial for prognostic assessment and treatment planning in OSCC. Recent research has suggested that nodal tumor volume (NTV) may be a more accurate indicator of nodal disease burden than traditional staging methods. However, the prognostic significance of NTV in OSCC remains unclear. This systematic review aims to evaluate the existing evidence on the relationship between NTV and prognosis in OSCC. A comprehensive search of electronic databases was conducted, and studies meeting inclusion criteria were critically appraised and synthesized. Our review identified 23 studies that investigated the prognostic significance of NTV in OSCC. The majority of studies reported that larger NTV was associated with poorer survival outcomes, although the strength of the association varied. The review also identified several areas for future research, including the standardization of NTV measurement and the integration of NTV into the broader landscape of OSCC management. In conclusion, our review suggests that NTV holds promise as a novel prognostic factor in OSCC, but more research is needed to fully elucidate its potential and inform clinical decision-making.